2008
DOI: 10.1016/j.jsat.2007.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences with high-dose naltrexone in patients with co-occurring cocaine and alcohol dependence

Abstract: This is a randomized, double blind, placebo-controlled clinical trial that evaluated the efficacy of a higher than typical daily dose of naltrexone (150mg/day), taken for 12 weeks, in 164 patients (n=116 men and n=48 women) with co-occurring cocaine and alcohol dependence. Patients were stratified by gender, and then randomly assigned to naltrexone or placebo, and to either cognitive behavioral therapy, or a type of medical management. The two primary outcomes were cocaine and alcohol use. Significant gender b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 74 publications
3
80
3
1
Order By: Relevance
“…This RCT also found a higher proportion of adverse effects among women treated with naltrexone (77%) than among those who received placebo (52%). Another RCT evaluated the efficacy of a higher dose of naltrexone compared to the typical one (150 mg instead of 50 mg per day) in 164 patients (48 women) with co-occurring cocaine and AD [62] . The results showed that men treated with naltrexone had reductions in cocaine and alcohol use and drug severity, whereas women did not benefit from this treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This RCT also found a higher proportion of adverse effects among women treated with naltrexone (77%) than among those who received placebo (52%). Another RCT evaluated the efficacy of a higher dose of naltrexone compared to the typical one (150 mg instead of 50 mg per day) in 164 patients (48 women) with co-occurring cocaine and AD [62] . The results showed that men treated with naltrexone had reductions in cocaine and alcohol use and drug severity, whereas women did not benefit from this treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, women with CD or PG are more likely to suffer from co-occurring depression and anxiety compared with men with these disorders (Granero et al, 2009;Greenfield et al, 2010;McCance-Katz et al, 1999). Finally, in CD, gender-differences have been reported in response to pharmacological treatments (Kosten et al, 1993;Pettinati et al, 2008) as well as in craving-related brain activations (Kilts et al, 2004;Li et al, 2005;Potenza et al, 2012), although the pattern of differences has been inconsistent. Considering gender-related influences on the neural correlates of craving/urge states may: (1) help resolve and better understand some of the apparent differences observed across studies to date; and (2) provide insight into genderrelated differences in brain function that might relate to important clinical differences observed in PG and CD.…”
Section: Introductionmentioning
confidence: 99%
“…None found any significant benefit for active medication (50mg/d [68,69], 100mg/d [54,55] 150mg/d [56]) in terms of outcomes for cocaine use, comorbid with alcohol, although this may have been masked by gender differences [56]. Pettinati et al [56] investigated the effect of naltrexone 150mg vs placebo as a relapse prevention agent, and found that at higher dose there was significantly greater reporting of nausea in the naltrexone group (53.7% vs. 26.8%, , p < 0.05), and in women more than men on the active medication (52.1% vs. 35.3%, , p < 0.05). A further analysis with 150mg/d [70] concluded that women with more severe psychiatric symptoms, and those with higher frequency of nausea were significantly more likely to discontinue treatment (OR = 23.89, and OR = 43.45, respectively), but the confidence intervals around these odds are broad.…”
Section: Cocaine and Alcohol Dependence (Cad)mentioning
confidence: 96%
“…Use of 150 mg naltrexone daily in patients with comorbid cocaine dependence [56] is discussed below, but a single open label study by Yoon et al [57] evaluated the safety of 150mg daily in patients with alcohol dependence (titrated up from 25mg daily by week 3) over eight weeks. All patients were given prochlorperazine 10mg to reduce nausea in the first 3 days and use of 'over-the-counter' analgesics was restricted, which may have affected the observation of raised transaminases in studies of higher dose naltrexone in pathological gamblers [58].…”
Section: About Herementioning
confidence: 99%
See 1 more Smart Citation